The outcomes of using flipped class strategy with first intermediate stage female students in the linguistic subjects - Alseayed, Eman Mohammed (Journal of Curriculum and Teaching Methodology, 2022)
The study is aimed to measure the effect of the flipped classroom strategy on teaching linguistic subjects upon the achievement of first-grade intermediate school students in one of Al-Ahsa Governorate schools. A sample of 32 students participated in the study. All participants were first-grade female students at the intermediate stage at the first semester of the academic year 1443 AH in the fifteenth intermediate school in Hofuf. The participants were divided conveniently into two groups: an experimental group which consisted of 16 students who studied using the flipped classroom strategy. The other group which consisted also of 16 students was a control group who studied using the traditional method. The research tool, which was an achievement test, was prepared by the author of this study, and its validity and reliability were confirmed. The results indicated that the differences between the experimental and control group average performance have no statistical significance (p>0.05). On the other hand, the study showed a significant increase in the scores of the excremental group after the implementation of the flipped classroom strategy. (p<0.05). The study concluded with a set of recommendations the most important of which: to hold training courses for teachers revolving around the use of the flipped classroom strategy in the educational process, with the use of modern technology and various educational platforms.